Cloud-Scale Archival Storage Using Ultrafast Laser Nanostructuring - Anderson, Patrick; Aranas, Erika B.; Armas, Jorge Rodriguez; Arslan, Ben; Assaf, Youssef; Behrendt, Raphael; Black, Richard; Bucciarelli, Stefano; Caballero, Marco; Cabara, Yoseline; Cameron, Pashmina; Chatzieleftheriou, Andromachi; et al. (Conference on Lasers and Electro-Optics, 2022)
Recent progress in ultrafast laser nanostructuring enables high-density multidimensional volumetric data writing. With exceptional media longevity, this could transform archival cloud storage. We demonstrate peak volumetric densities above 250 MB/mm 3 of data write and read.